Предмет: Математика,
автор: evzheney
Решите уравнение (x-2)(x^2+6x+9)=6(x+3)
Ответы
Автор ответа:
0
(x-2)(x+3)² - 6(x+3) = 0
(x+3) · [(x-2)(x+3)-6)] =0
a) x+3=0 ⇒ x= -3
b) x²-2x+3x-6 -6 =0
x² + x - 12 = 0
(x-3)(x+4)=0 ⇒ x2=3 ; x3 = -4
Ответ: x={-4; -3; 3}
(x+3) · [(x-2)(x+3)-6)] =0
a) x+3=0 ⇒ x= -3
b) x²-2x+3x-6 -6 =0
x² + x - 12 = 0
(x-3)(x+4)=0 ⇒ x2=3 ; x3 = -4
Ответ: x={-4; -3; 3}
Похожие вопросы
Предмет: Математика,
автор: angelina4586
Предмет: Математика,
автор: Zackomania
Предмет: Математика,
автор: kkozitsyna
Предмет: Математика,
автор: anna555k
Предмет: География,
автор: kirillkarablin